Validation of a stoma‐specific quality of life questionnaire in a sample of patients with colostomy or ileostomy. (November 2013) - Canova, C.; Giorato, E.; Roveron, G.; Turrini, P.; Zanotti, R.
Abstract Aim The aim of this study was to determine how socio‐demographic and clinical variables affect quality of life (QoL) and to assess the validity of a 20‐item scale in a sample of Italian subjects with colostomy, ileostomy and multiple stomata. Method A cross‐sectional multicentre survey was carried out in Italy between 2009 and 2010 in 73 stoma centres coordinated by the University of Padova. Patients aged 18 years old and above with a history of nontemporary stoma were included in the study. The Stoma Care QoL scale was measured and validated using a Rasch model. Socio‐demographic and clinical characteristics were considered in the analyses. Results Two hundred and fifty‐one patients were recruited for the study; the mean age was 62 years, 58% were men, 72% had colostomy and 25% ileostomy; approximately 70% of patients had intestinal cancer requiring a stoma, 13% a complication and 10% an inflammatory disease. No significant differences were observed throughout strata in the Stoma Care QoL scale index, except for geographical area, where subjects from south Italy showed a significantly lower index than subjects living in other parts of Italy (P < 0.01). Colostomy and ileostomy patients reported very similar QoL. Cronbach's alpha for the Stoma Care QoL scale was 0.90 (95% CI 0.88–0.92). Rasch analysis supported the viability of the Stoma Care QoL scale questionnaire and showed acceptable goodness‐of‐fit. Three under‐fitted items were observed. Conclusion The study confirms the validity of the 20‐item Stoma Care QoL scale questionnaire as a research tool for stoma patients but the number of items could be reduced.